Strategi Bersaing Perusahaan Taksi Dalam Menghadapi Perubahan Lingkungan - Ahmad Saifi Athoillah; Muhammad Firdaus; Bunasor Sanim (CAPITAL: Jurnal Ekonomi dan Manajemen, 2019)
This study aimed to analyze the satisfaction of taxi passengers, analyze the internal and external factors in PT A and formulate the competitive strategy with conventional taxi competitor and online taxi companies. The scope og this research is specifically focused on the competitive staretgy at strategic business unit level. This study is uses quantitative and quantitative descriptive approach. Data analysis techniques used are porter five score model, IFE, EFE, IE and QSPM. The results of this study on the analysis of IFE, PT A shows that the highest strength is on a strong, strategic distribution network of taxi in big cities. Meanwhile, the highest threat is standardization of tariff, number of taxi, and minimum identify of online taxi. Furthermore, IE matrix analysis shows that PT A is in quadrant I (grow and build strategy). The decision making stage with QSPM matrix has the order of strategic prority as follows: forward integration, backward integration, horizontal integration, product development, market penetration, and market development.Keywords: EFE, IFE, IPA, QSPM, competitive strategy